Implementasi Kebijakan BPJS Kesehatan Di Kota Surabaya (Studi Tentang Kepesertaan PBI Jaminan Kesehatan Dalam Mengakses Pelayanan Kesehatan) - Masadib Akmal Vyandri; Rudy Handoko (DIA: Jurnal Administrasi Publik, 2014)
BPJS health targets for member PBI provide convenience for participants in accessing health services financed by the government, the principle of prudence sustainable BPJS transparency in financial management. The purpose of this study is to describe, analyze and Interpret the implementation of Program Policy BPJS using a model approach to the implementation of policies of George Edward III and Develop policy model in implementation program is effective and efficient BPJS appropriate purpose to provide health services to poor people in Surabaya. This research was conducted using qualitative method. Implementation begins with socialization to the provider of health services such as health centers and hospitals. Financing members funded by PBI budget Surabaya Surabaya Goverment through the budget to the health budget. Membership data collection continued through cooperation between Bapemas and the Department of Health to add and remove members of PBI budget Surabaya. Health Department will continue its coordination and supervision of health care providers and handles complaints from members of PBI.Keywords: health care, Implementation, Poverty, BPJS, Surabaya